Capital Structure, Firm Size, and Operational Efficiency on Financial Performance with Good Corporate Governance as a Moderating Variable: Evidence from Indonesian Plastic and Packaging Firms in an Emerging Market Context - Gusmarila Eka Putri; Agus Ismaya Hasanudin; Imam Abu Hanifah; Munawar Muchlish (Indonesian Journal of Taxation and Accounting, 2026)
Purpose–  This study investigates the determinants of financial performance in the Indonesian plastic and packaging sector by examining the roles of capital structure, firm size, and operational efficiency, with Good Corporate Governance (GCG) as a moderating variable. In cost-sensitive industries characterized by high input volatility, firms often face challenges in translating growth into profitability, making efficiency and governance increasingly critical. Methods – Using a quantitative approach, this study analyzes secondary panel data from 40 firm-year observations during the 2019–2022 period and applies panel data regression combined with Moderated Regression Analysis (MRA). Findings – The results indicate that capital structure and operational efficiency have negative and significant effects on financial performance, suggesting that higher leverage and inefficiency increase financial burden and reduce profitability. In contrast, firm size does not have a significant effect, implying that larger scale does not necessarily improve efficiency due to increased complexity and coordination costs. Furthermore, GCG demonstrates a mixed moderating role, where it significantly weakens the relationship between capital structure and financial performance but does not significantly moderate the effects of firm size and operational efficiency. Research implications – These findings highlight that in emerging market contexts, financial structure and inefficiency tend to act as risk signals rather than value-enhancing mechanisms, emphasizing the importance of cost control and effective governance practices in improving firm performance. Originality – This study offers original empirical evidence by integrating capital structure, firm size, and operational efficiency with Good Corporate Governance as a moderating variable to explain financial performance in Indonesian plastic and packaging firms within an emerging market context.